Transition to Inclusive Education Systems According to the Convention on the Rights of Persons with Disabilities. Issue 1 (2nd January 2016) - de Beco, Gauthier
ABSTRACT: This article deals with the transition to inclusive education systems and therefore concerns states that have built segregated education systems. Article 24 of the Convention on the Rights of Persons with Disabilities (CRPD) proclaims the right to inclusive education for disabled people. State parties that are equipped with special schools, however, face particular challenges in progressively realising the right in question. This article therefore examines what 'inclusive education' truly means, what steps must be taken to achieve it, and what tools can be used to ensure the transition to inclusive education systems so as to comply with the CRPD. Considering the obstacles to inclusive education, the article argues that inclusive education is a process that needs permanent efforts to adapt the general education system to disabled children. It also considers the implementation of the right of disabled people to education through the adoption of national human rights action plans and the use of human rights indicators.